Pelatihan Pembuatan LKPD Dengan Pendekatan Kontekstual Bagi Guru SMP - Bettri Yustinaningrum; Lola Mandasari (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The independent curriculum requires teachers to have an enthusiastic, active, innovative, creative, and skilled attitude. One form of innovation for teachers is to create LKPD with a contextual approach that encourages students to be active and creative. However, the LKPD made by teachers is still in the form of questions and exercises that only measure the ability to answer right or wrong, and the concepts are not yet linked to students' real lives. Thus, the purpose of this service is to train junior high school math teachers in creating LKPD using a contextual approach. CBR is the method used in this service, along with practice techniques, Q&A sessions, and lectures. The three stages of an activity are preparation, execution, and evaluation. The results of the service showed that participants were able to understand and create LKPD using a contextual approach. This can be seen from the results of the pre-test and post-test evaluations that have been carried out. Apart from that, based on the service activity questionnaire that was distributed to participants, they received a positive response, and participants wanted sustainable service activities.